2021
DOI: 10.35631/ijepc.642038
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Ethnocultural Empathy and Organizational Citizenship Behavior (Ocb) Among Public Servants in Sabah

Abstract: Organizational citizenship behavior (OCB) throughout literature provides evidence that benefits both employees and the organizations in terms of increasing the level of employees' well-being, work satisfaction, customers' satisfaction as well as the quality of work performance. Hence, it is important to understand the possible reasons behind the occurrence of OCB to increase the likelihood of employees engaging in OCB. Based on the prosocial motivational concept, empathy is the main motivator to helping behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Podsakoff et al (2009) showed a strong link between OCBs and low employee turnover and absenteeism and high productivity and efficiency. Other research has identified predictors such as satisfaction (e.g., Chan & Lai, 2017;Batra & Kaur, 2021), motivation (e.g., Joo & Jo, 2017;Somech & Khotaba, 2017), productivity (e.g., Ismael et al, 2022;Kataria & Adhikari, 2022), autonomy (e.g., Akram et al, 2017), quality of work (Osman et al, 2021); and commitment (e.g., Hu et al, 2017). OCBs also contribute to the creation of a psychologically healthy work environment by (a) stimulating the development of interpersonal relationships, (b) avoiding creating difficult situations for others, (c) demonstrating a high tolerance to adverse situations (e.g., a lack of respect and fairness), (d) agreeing to abide by the rules and laws governing the organization's activity, and (e) voluntarily getting involved in the informal social and cultural events at the organization (Osman et al, 2021;Popescu et al, 2018).…”
Section: Ocbsmentioning
confidence: 99%
“…Podsakoff et al (2009) showed a strong link between OCBs and low employee turnover and absenteeism and high productivity and efficiency. Other research has identified predictors such as satisfaction (e.g., Chan & Lai, 2017;Batra & Kaur, 2021), motivation (e.g., Joo & Jo, 2017;Somech & Khotaba, 2017), productivity (e.g., Ismael et al, 2022;Kataria & Adhikari, 2022), autonomy (e.g., Akram et al, 2017), quality of work (Osman et al, 2021); and commitment (e.g., Hu et al, 2017). OCBs also contribute to the creation of a psychologically healthy work environment by (a) stimulating the development of interpersonal relationships, (b) avoiding creating difficult situations for others, (c) demonstrating a high tolerance to adverse situations (e.g., a lack of respect and fairness), (d) agreeing to abide by the rules and laws governing the organization's activity, and (e) voluntarily getting involved in the informal social and cultural events at the organization (Osman et al, 2021;Popescu et al, 2018).…”
Section: Ocbsmentioning
confidence: 99%
“…Javanese culture and the dominant group's privilege are highlighted by this. According to Osman, Ghani & Alis, (2021), dominant ethnic groups play important roles in society, especially when they maintain their social superiority. Political factions that seek equality challenge the majority group's power in democratic administration.…”
Section: Acceptance Of Culture Differencesmentioning
confidence: 99%
“…Inter-group conflict in Indonesia can be seen in the past and possibly ongoing violence between the indigenous Javanese and the Chinese community in Surakarta, Central Java (Osman, Ghani & Alis, 2021).…”
Section: Introductionmentioning
confidence: 99%